Functional movement development across the life span - Cech, Donna J. PT, DHS, Certified Specialist in Pediatric physical Therapy (PCS); Martin, Suzanne "Tink" PT, PhD; Staples, William H. PT, DHSc, DPT, Clinical Specialist in Geriatric Physical Therapy (GCS), FAPTA
Evidence-based information on functional movement development, health, and wellness across the life span. Providing a solid foundation in the normal development from both a systems and function perspective, this comprehension resource helps you maximize a patient's functional movement abilities across the life span